DAYA HASIL BEBERAPA KULTIVAR PADI GOGO LOKAL ASAL SULAWESI TENGGARA PADA CEKAMAN KEKERINGAN - Sadimantara, Gusti Ray; Muhidin, Muhidin (Jurnal Agroteknos, 2012)
Demand for rice as a source of food continues to rise, while the capacity to produce a rice paddy more limited. One effort is to develop upland rice tolerance to drought and high production potential. The study was conducted at the Experimental Faculty of Agriculture Unhalu. Character judgments production were observed between (1) the number of tillers at harvest, (2) the number of productive tillers, (3) panicle length (cm), (4) the number of filled grain/panicle  and  seed  weight  of  100  grains.  The  results  showed  that  there  are  two varieties that are very resistant to drought conditions, namely Bali and Wangkariri Sala. While five local upland rice varieties are very sensitive to drought are varieties Paebiu Sitoro, Wagamba, Paebiu Angata, Apolo, Wakawondu. Keywords: drought resistance, drought stress, upland rice.